Analysis of the effects of platelet-rich plasma injection on the human body depending on the site of administration – review article - Przeradzki, Jakub; Lubczyńska, Zuzanna; Kotulska, Maria; Lichman, Martyna; Rząd, Katarzyna; Borycka, Aleksandra; Potocka, Zofia; Laskus, Paulina; Jędrzejewska, Barbara; Wieliński, Łukasz (Journal of Education, Health and Sport, 2023)
Introduction: Platelet-rich plasma (PRP) is an autologous material. It is created by drawing the patient’s blood and preparing it properly. In that, a several-fold increase in platelets and growth factors is achieved. By applying the PRP prepared this way to the appropriate tissue, it is possible to improve the clinical condition of many disorders. Purpose: Analysis of the effects of platelet-rich plasma injection on the human body depending on the site of administration. Review of literature. Material and methods: We have selected, in our opinion, the most important information from articles about the use of PRP in: androgenetic alopecia, hair regrowth, wound healing, atrophic acne scars, erectile dysfunction, gynecology and improving women’s sexual satisfaction, osteoarthritis and skin rejuvenation. Summary (conclusion): Thanks to its properties, platelet-rich plasma (PRP) can stimulate the human body to regenerate. Androgenetic alopecia, hair regrowth, acceleration of wound healing, acne scars, erectile dysfunction and osteoarthritis are just some of the disorders in which the use of platelet-rich plasma proves to be promising. From the studies above it can be concluded that the effects of local PRP injections can be complementary to the therapy of many other diseases. However, more adequate research is needed to register the application of local platelet-rich plasma as a form of treatment for these diseases.